PROSPEK EKSPOR KOPI ARABIKA ORGANIK BERSERTIFIKAT DI KABUPATEN ACEH TENGAH - Lukman Hakim; Andika Septian (Jurnal Agrisep, 2011)
Export Prospects the Certified Organic Coffee Arabica at Central Aceh DistrictABSTRACT. This study was aimed to determine the export prospects of the certified organic coffee Arabica at Central Aceh district in the future. The object of study was secondary data related to export activity of the certified organic coffee Arabica in that district. The sampling method was a periodic data (time series), and trend analysis. The result showed that the export activity of the certified organic coffee Arabica has been started since August 2006 concurrently with receiving a certification from "Fair Trade" as an official International of Certificate Organization. By obtaining that certification, it contributes to establish and settle the position of produced coffee from plateau Gayo in coffee Arabica worldwide market. Result of trend analysis indicated that the volume and value of the export of the certified organic coffee will increase in the future, although in nominal value has fluctuations and varies, but it remained showing the positive improvement. Prospects of the coffee from Central Aceh depend on support of variables in exporting itself, such as market expansion to other countries (USA is the biggest coffee importer), the product efficiency, the suppression export costs, as well as improvement of the quality of this coffee.